Genotypic Expansion Within the Population Structure of Classical Brucella Species Revealed by MLVA16 Typing of 1404 Brucella Isolates From Different Animal and Geographic Origins, 1974–2006 - Vergnaud, Gilles; Hauck, Yolande; Christiany, David; Daoud, Brendan; Pourcel, Christine; Jacques, Isabelle; Cloeckaert, Axel; Zygmunt, Michel S. (Frontiers in Microbiology, 2018)
Previous studies have shown the usefulness of MLVA16 as a rapid molecular identification and classification method for Brucella species and biovars including recently described novel Brucella species from wildlife. Most studies were conducted on a limited number of strains from limited geographic/host origins. The objective of this study was to assess genetic diversity of Brucella spp. by MLVA16 on a larger scale. Thus, 1404 animal or human isolates collected from all parts of the world over a period of 32 years (1974-2006) were investigated. Selection of the 1404 strains was done among the approximately 4000 strains collection of the BCCN (Brucella Culture Collection Nouzilly), based on classical biotyping and on the animal/human/geographic origin over the time period considered. MLVA16 was performed on extracted DNAs using high throughput capillary electrophoresis. The 16 loci were amplified in four multiplex PCR reactions. This large scale study firstly confirmed the accuracy of MLVA16 typing for Brucella species and biovar identification and its congruence with the recently described Extended Multilocus Sequence Analysis (MLSA). In addition, it allowed identifying novel MLVA11 (based upon 11 slowly evolving VNTRs) genotypes representing an increase of 15 % relative to the previously known Brucella MLVA11 genotypes. Cluster analysis showed that among the MLVA16 genotypes some were genetically more distant from the major classical clades. For example new major clusters of B. abortus biovar 3 isolated from cattle in Sub-Saharan Africa were identified. For other classical species and biovars this study indicated also genotypic expansion within the population structure of classical Brucella species. MLVA proves to be a powerful tool to rapidly assess genetic diversity of bacterial populations on a large scale, as here on a large collection of strains of the genomically homogeneous genus Brucella. From this point of view the highly discriminatory power of MLVA appears of particular interest as a first step for selection of Brucella strains for whole-genome sequencing. The MLVA data of this study were added to the public Brucella MLVA database at http://microbesgenotyping.i2bc.paris-saclay.fr. Current version Brucella_4_3 comprises typing data from more than 5000 strains including in silico data analysis of public whole genome sequence datasets.